Metode Simple Additive Weighting Untuk Menentukan Jumlah Persedian Stok Obat Tbc Pada Puskesmas Bagan Asahan - Sela, Dhea; Hasugian, Abdul Halim (LPPM Universitas Dinamika Bangsa, 2024)
The availability of adequate drugs is very important in maintaining the quality of health services at the Bagan Asahan Health Center, especially for the treatment of TB disease. One of the main challenges faced is determining the right amount of TB drug stock to prevent shortages or excess stock, which can affect the effectiveness of services to patients. To overcome this problem, this study uses the Simple Additive Weighting (SAW) method implemented in a web-based decision support system. This system is designed to assist in determining the amount of drug stock needed accurately based on data collected from the Bagan Asahan Health Center. The data analyzed includes drug demand in the previous month and the final amount of drug stock. Through the SAW method, the data is processed to produce a drug ranking and prioritize the required stock replenishment. This study aims to provide a system that is not only efficient and structured, but also helps health workers in managing drug supplies optimally, thereby increasing accuracy in stock replenishment and efficiency in the drug procurement process. The results of testing through simulation and real data analysis show that this system is able to provide more accurate recommendations for drug stock management. In addition, this system is able to produce periodic stock reports, which can be used by health center management to make drug procurement decisions appropriately and efficiently.